2020
DOI: 10.1093/botlinnean/boaa087
|View full text |Cite
|
Sign up to set email alerts
|

Unity in diversity: phylogenetics and taxonomy of Rhabdoweisiaceae (Dicranales, Bryophyta)

Abstract: Molecular phylogenetic reconstructions of Rhabdoweisiaceae based on plastid (trnS-rps4 and trnL-F) and mitochondrial (nad5) DNA sequences and a comprehensive taxon sampling were performed, including 15 out of 16 genera currently attributed to the family, taxa recently found belonging to Rhabdoweisiaceae and expanded outgroups from related families of Dicranidae. The suggested revised delimitation of the family comprises Camptodontium (previously referred to Dicranaceae), three subaquatic species currently clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
4
19
0
1
Order By: Relevance
“…The specimen referred here to Arctoa hyperborea was sterile and its identification is based on DNA sequence data. Nuclear ITS as well as plastid markers rps4 and trnL and mitochondrial Nad5 from this specimen were nearly identical to specimens of A. hyperborea from Novaya Zemlya Archipelago (see Fedosov et al, 2020). Gametophyte morphology meets this species as well, therefore we refer our specimen to A. hyperborea.…”
Section: A B F E C D G Hsupporting
confidence: 53%
“…The specimen referred here to Arctoa hyperborea was sterile and its identification is based on DNA sequence data. Nuclear ITS as well as plastid markers rps4 and trnL and mitochondrial Nad5 from this specimen were nearly identical to specimens of A. hyperborea from Novaya Zemlya Archipelago (see Fedosov et al, 2020). Gametophyte morphology meets this species as well, therefore we refer our specimen to A. hyperborea.…”
Section: A B F E C D G Hsupporting
confidence: 53%
“…Epiphytic lineages in Syntrichia are characterized as small plants with bulbiform leaf arrangement when dry (Figure 2), a short extension of the costa, presence of asexual propagules, and reduced size of basal cells similar to the majority of epiphytic pleurocarpous (Hedenäs, 2012b). In other unrelated mosses, this phenomenon has been called the epiphytism syndrome to characterize plants with a set of distinctive morphology (Fedosov et al, 2021). Mosses have also shown differentiation of perichaetial leaves (Tubanova et al, 2019) and/or distinct ornamentation of peristomes (Vanderpoorten et al, 2002; Hedenäs, 2012b), associated with a transition to epiphytic conditions (Fedosov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In other unrelated mosses, this phenomenon has been called the epiphytism syndrome to characterize plants with a set of distinctive morphology (Fedosov et al, 2021). Mosses have also shown differentiation of perichaetial leaves (Tubanova et al, 2019) and/or distinct ornamentation of peristomes (Vanderpoorten et al, 2002; Hedenäs, 2012b), associated with a transition to epiphytic conditions (Fedosov et al, 2021). For instance, the uncommon fertile condition of S. papillosa and sect.…”
Section: Discussionmentioning
confidence: 99%
“…D. staphylina has a fairly typical dicranoid peristome with triangular, in basal and median part longitudinally striolate rather than filiform teeth, split to half of their length into unequal lobes, without a basal membrane ( Figure 2 ), which clearly fits the description of the dicranoid peristome type by [ 28 ]. This favors the idea of including this lineage in the delimitation of Dicranales, rather than establishing an isolated new order to accommodate it, suggesting that the dicranoid peristome is the plesiomorphic character state for the whole large lineage, from which the more derived peristomes in Grimmiales and Pottiaceae evolved (see also [ 9 ] for a discussion of the secondarily modified peristomes in, e.g., Glyphomitrium Brid. or Pseudoblindia Fedosov, M. Stech & Ignatov of Rhabdoweisiaceae).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular phylogenetic studies of bryophytes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] have shown that the traditional morphology-based circumscriptions of genera are often biased by morphological convergence and in reality comprise a suite of phylogenetically unrelated lineages. This is especially the case for genera with reduced morphology, such as pioneer species with short life cycles, e.g., Entosthodon Schwägr.…”
Section: Introductionmentioning
confidence: 99%